Gestalt Perceptual Organization of Visual Stimuli Captures Attention Automatically: Electrophysiological Evidence - Marini, Francesco; Marzi, Carlo A. (Frontiers in Human Neuroscience, 2016)
The visual system leverages organizational regularities of perceptual elements to create meaningful representations of the world. One clear example of such function, which has been formalized in the Gestalt psychology principles, is the perceptual grouping of simple visual elements (e.g., lines and arcs) into unitary objects (e.g., forms and shapes). The present study sought to characterize automatic attentional capture and related cognitive processing of Gestalt-like visual stimuli at the psychophysiological level by using event-related potentials (ERPs). We measured ERPs during a simple visual reaction time task with bilateral presentations of physically matched elements with or without a Gestalt organization. Results showed that Gestalt (vs. non-Gestalt) stimuli are characterized by a larger N2pc together with enhanced ERP amplitudes of non-lateralized components (N1, N2, P3) starting around 150ms post-stimulus onset. Thus, we conclude that Gestalt stimuli capture attention automatically and entail characteristic psychophysiological signatures at both early and late processing stages.